Kt/V urea y mortalidad en pacientes en hemodiálisis del Hospital Regional de Loreto, 2023-2024 - Flórez Vela, Milagros (2025)
Introduction: Chronic kidney disease represents a significant cause of morbidity and mortality worldwide, particularly in countries with limited resources. Hemodialysis is an essential replacement therapy for patients in end-stage renal disease, and its effectiveness is evaluated through the Kt/Vurea index. This parameter, by measuring urea clearance during dialysis, is closely associated with patient survival. At the Regional Hospital of Loreto, there were no updated data regarding dialysis adequacy or its relationship with mortality, which justified the implementation of this study. Objective: To determine the relationship between the Kt/Vurea index and mortality in patients undergoing hemodialysis at the Regional Hospital of Loreto during the period 2023 – 2024. Methods: Observational, analytical, retrospective, and correlational study. Population: The sample was selected through census sampling and included 121 patients who met the inclusion criteria. Results: A total of 52.1% of patients on hemodialysis achieved a Kt/Vurea ≥1.2, while 47.9% remained with suboptimal values. Significant associations were found between Kt/V < 0.001), age group 40 – 65 years (p = 0.037), overweight status (p = 0.036), and deceased status (p = 0.043). The mortality rate was 40.5% and was significantly associated with arterial hypertension (p = 0.039), type 2 diabetes mellitus (p = 0.045), catheter-related infection (p = 0.025), and suboptimal Kt/V (p = 0.043). The Kaplan–Meier survival analysis showed a more rapid decline in the group with Kt/V <1.2, with a statistically significant difference according to the Log Rank test (p = 0.0421). Conclusions: Patients with low Kt/V urea have a higher risk of death; this was observed in the Kaplan–Meier survival analysis and confirmed by the Log-Rank test (p = 0.0421). Nearly half of the patients (47.9%) had low Kt/V urea, which indicates they were receiving poor-quality hemodialysis. Being diabetic (type 2), aged between 40 and 65 years, or having had an infection in the central venous catheter were identified as predictors of death. In addition, male patients, those who were overweight, or those aged between 40 and 65 years frequently had low Kt/V urea.